Fermentation, Purification, and Tumor Inhibition of a Disulfide-Stabilized Diabody Against Fibroblast Growth Factor-2 - Zhang, Simin; Huang, Jiahui; Zhang, Ligang; Gu, Jiangtao; Song, Qifang; Cai, Yaxiong; Zhong, Jiangchuan; Zhong, Hui; Deng, Yanrui; Zhu, Wenhui; Zhao, Jianfu; Deng, Ning (Frontiers in Oncology, 2021)
Angiogenesis is considered one of the hallmarks of cancer and plays a critical role in the development of tumor. Fibroblast growth factor 2 (FGF-2) is a member of the FGF family and participates in excessive cancer cell proliferation and tumor angiogenesis. Thus, targeting FGF-2 was considered to be a promising anti-tumor strategy. A disulfide-stabilized diabody (ds-Diabody) against FGF-2 was produced in Pichia pastoris (GS115) by fermentation and the anti-tumor activity was analyzed. The novel 10-L fed batch fermentation with newly designed media was established and the maximum production of the ds-Diabody against FGF-2 reached 210.4 mg/L. The ds-Diabody against FGF-2 was purified by Ni2+ affinity chromatography and DEAE anion exchange chromatography. The recombinant ds-Diabody against FGF-2 could effectively inhibit proliferation, migration and invasion of melanoma and glioma tumor cells stimulated by FGF-2. Furthermore, xenograft tumor models assays showed that the ds-Diabody against FGF-2 had potent antitumor activity in nude mice by inhibiting tumor growth and angiogenesis. The tumor growth inhibition rate of melanoma and glioma was about 70% and 45%, respectively. The tumor angiogenesis inhibition rate of melanoma and glioma was about 64% and 51%, respectively. The results reveled that the recombinant ds-Diabody against FGF-2 may be a promising anti-tumor drug for cancer therapy.